Persistence, the transmission mechanism and robust monetary policy - Ignazio Angeloni; Günter Coenen; Frank Smets (European Central Bank (ECB), 2003)
In this paper we first explore the impact of nominal and real persistence on the transmission process of various shocks in an estimated DSGE model of euro area. We then analyse its impact on optimal monetary policy and investigate the performance of various monetary policies when the policy maker is uncertain about the degree of nominal and real persistence.
Keywords: E4; E5; 330; euro area; monetary policy; Persistence; transmission process